PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN FAVE HOTEL S. PARMAN MEDAN - Dwi Santoso, Jarwo; Pebrina, Asti; Simatupang, Sabar LT.; Tarigan, Jenni (JURNAL GLOBAL MANAJEMEN, 2023)
The realization of the vision and mission of an organization is determined by the performance and effectiveness of its employees in carrying out the assigned duties and responsibilities. Organizations and companies generally expect their employees to be able to carry out assigned tasks efficiently, productively and professionally. This type of research is quantitative research using multiple linear regression methods with a population and sample of 36 employees, using primary data and direct sources from Fave Hotel S. Parman Medan staff. The results of the regression test yield Y = 7.497 + 0.260X1 + 0.516X2 which means that any increase in the leadership and work discipline variables will also have an impact on the performance variable. Based on the results of the partial test of the leader variable, the value of t-count (6.543) > t-table (1.688), sig 0.000 <0> t-table (1.688), sig 0.000 <0> F-table (3.18), sig Array 0.000 <0> F(3.18), sig 0.000 <0> 0.05. meaning that the variables of leadership and work discipline simultaneously or jointly influence the performance variables.